Pengaruh Kualitas Produk, Persepsi Harga, Dan Kepuasan Konsumen Terhadap Keputusan Pembelian Berkelanjutan Fried Chicken Rizky Di Kota Balikpapan - Ovigeria Subroto Sinaga; Tiara Maharani (Science and Education Journal (SICEDU), 2026)
This study aims to analyze the effect of product quality, price perception, and customer satisfaction on sustainable purchase decisions at Fried Chicken Rizky in Balikpapan City. This research employed a quantitative approach using multiple linear regression analysis. The research sample consisted of 107 respondents who are consumers of Fried Chicken Rizky, selected using a purposive sampling technique, with data collected through a Likert-scale questionnaire. The results indicate that product quality (X1), price perception (X2), and customer satisfaction (X3) each have a significant partial effect on sustainable purchase decisions. Simultaneously, the three variables have a significant effect with an Adjusted R² = 0.649, meaning 64.9% of the variation in sustainable purchase decisions is explained by the three variables. Product quality is the most dominant variable influencing the sustainable purchase decisions of Fried Chicken Rizky consumers in Balikpapan City. Keywords: Product Quality, Price Perception, Customer Satisfaction, Sustainable Purchase Decision